PENGEMBANGAN MEDIA DADU BERBASIS NUANSA ISLAMI UNTUK MELATIH KREATIVITAS PESERTA DIDIK KELAS III SD/MI - Andika Surya Perdana; Nur Azmi Alwi; Yulia Maulani (Cerdas Proklamator, 2022)
This study aims to develop dice media that has been developed by previous researchers, the development of previous media has not been effective in its use and there is no Islamic nuance and creativity skills in the learning media, so this research develops dice media based on Islamic nuances on the theme of growth and development of living things. to train the creativity of third grade SD/MI students. This research is also to find out how the expert opinion on dice media based on Islamic nuances on the theme of growth and development of living things to train the creativity of third grade elementary school / MI students and find out the response of educators to dice media based on Islamic nuances on the theme of growth and development of living things to train student creativity. From the research conducted, the opinions of experts on the dice media with Islamic nuances on the theme of growth and development of living things to train the creativity of students got very valid and practical criteria, with an average assessment of media experts of 90.12%, linguists' assessments of 86 ,6% and material/content expert assessment 87,13%. The response of educators to the dice media with Islamic nuances to train the creativity of students received an assessment of 91.36%. The results of this study indicate that the dice media based on Islamic nuances to train the creativity of students on the theme of growth and development of living things in class III SD/MI can be used as learning media.